2023
DOI: 10.1021/acsnano.2c10453
|View full text |Cite
|
Sign up to set email alerts
|

In-Tumor Biosynthetic Construction of Upconversion Nanomachines for Precise Near-Infrared Phototherapy

Abstract: Targeted construction of therapeutic nanoplatforms in tumor cells with specific activation remains appealing but challenging. Here, we design a cancer-motivated upconversion nanomachine (UCNM) based on porous upconversion nanoparticles (p-UCNPs) for precise phototherapy. The nanosystem is equipped with a telomerase substrate (TS) primer and simultaneously encapsulates 5-aminolevulinic acid (5-ALA) and d-arginine (d-Arg). After coating with hyaluronic acid (HA), it can readily get into tumor cells, where 5-ALA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…TEM images revealed that CuH was nonspherical and agglomerated, which was distinct from HCP (Figure S8), and CuH-PVP possessed worse dispersibility than HCP despite that they were similar in shape (Figure S9), which was ascribed to massive hydroxyl groups (−OH) from HA. 35 Zeta potential images display continuously decreasing potentials after adding PVP scaffolds and wrapping HA (Figure 1G), which was in accordance with the negative potentials of PVP and HA. Furthermore, the Fourier transform infrared (FT-IR) spectra exhibited characteristics of PVP and HA at colored zones, including amorphous H 2 O and −OH characteristic absorption (zone I), −C−H− stretching vibrations (zone II), −C�O and antisymmetric −COOH stretching vibrations (zone III), −C− N− and symmetric −COOH stretching vibrations (zone IV), and CuH and saccharide characteristic absorption (zone V) peaks (Figure 1H), 31,34 suggesting the successful fabrication of CuH-PVP and HCP.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…TEM images revealed that CuH was nonspherical and agglomerated, which was distinct from HCP (Figure S8), and CuH-PVP possessed worse dispersibility than HCP despite that they were similar in shape (Figure S9), which was ascribed to massive hydroxyl groups (−OH) from HA. 35 Zeta potential images display continuously decreasing potentials after adding PVP scaffolds and wrapping HA (Figure 1G), which was in accordance with the negative potentials of PVP and HA. Furthermore, the Fourier transform infrared (FT-IR) spectra exhibited characteristics of PVP and HA at colored zones, including amorphous H 2 O and −OH characteristic absorption (zone I), −C−H− stretching vibrations (zone II), −C�O and antisymmetric −COOH stretching vibrations (zone III), −C− N− and symmetric −COOH stretching vibrations (zone IV), and CuH and saccharide characteristic absorption (zone V) peaks (Figure 1H), 31,34 suggesting the successful fabrication of CuH-PVP and HCP.…”
Section: Resultssupporting
confidence: 73%
“…FITC molecules were encapsulated into HCP as fluorescent probes (excitation, 494 nm and emission filter, 520 nm) for cellular uptake observation. 35 Then, 10 μL of FITC solution (10 mg/mL, dissolved by DMSO buffer) was added into 1 mL BSA solution (10 mg/mL, dissolved by HEPES buffer) and the mixed solution was kept oscillating at 4 °C overnight. After that, we put 300 μL of mixed solution into the CuH-PVP solution (100 μg/mL, 3 mL) and mixed the solution by ultrasonication in the dark for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular 1 O 2 generation was evaluated using 2′,7′dichlorodihydrofluorescein diacetate (DCFH-DA) as an indicator, which emits green fluorescence after being oxidized by 1 O 2 . 46 As shown in Figure 5a, HeLa cells alone showed a negligible fluorescence signal after irradiation by the 635 nm laser.…”
Section: Resultsmentioning
confidence: 99%
“…ADPA was chosen as another 1 O 2 indicator to evaluate the photodynamic property of InTPP self-assemblies under 635 nm laser irradiation. ADPA (50 μL, 10 −4 mol/L) was added into different InTPP self-assembled aqueous solutions with the same InTPP molecule concentration (4 μg/mL), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…DNA nanomachine, a new class of molecular nanomachines with self-propelled movement, played a significant role in biomolecular transport and catalysis, biosensor construction, etc., due to highly programmable functionalities and biocompatibility. In the traditional DNA nanomachine, compared with 1D and 2D DNA nanomachines with limited functional domains leading to low working efficiency, 3D DNA nanomachines can load much more functional molecules to improve the working efficiency to some extent; however, restricted by the inherent weak driving force of Brownian motion, the 3D DNA nanomachine also suffered from the slow moving rate, which was the main obstacle of traditional DNA nanomachine . Therefore, it remains a challenge to find an extra driving force to accelerate the movement of 3D nanoparticle-based DNA nanomachine for obtaining a much higher working efficiency.…”
Section: Introductionmentioning
confidence: 99%